(untitled) (Medical Forum Monthly, 2024)
Objective: To compare the signs and symptoms of Medulloblastomas and Desmoblastic Medulloblastomas. Study Design: Retrospective study Place and Duration of Study: This study was conducted at King Khalid University Hospital, Rayadh, Saudi Arabia from 1st January 2001 till 31st December 2010. Materials and Methods: Total of 37 patients were included in the study. After taking written consent from all the patients or their relatives, this study was conducted. Permission was also taken from the ethical committee of the hospital. 37 patients were included in the study. Result: Percentage of important symptoms of intracranial tumors like headache, reduced vision and hydrocephalus was comparatively higher in medulloblastomas as compare to desmoblastic medulloblastomas. None of the desmoblastic variety had metastasis on presentation, hence all of them completely excised. Unfortunately, we were able to excise only 82.14% of medulloblastomes. 14.28% were partially excised while in 3.57% of cases, surgeon was only able to take biopsy. Conclusion: Desmoblastic variety of medulloblastoma had better prognosis as compare to Classical Medullblastoma.